Macronutrientes y su relación con la antropometría en niños de 6 a 36 meses de la parroquia San Pedro de la Bendita, cantón Catamayo - Lapo Díaz, Melany Patricia (2019)
The consumption of micronutrients in the infant and pre-school stage favors their growth and development, the functioning of the organism and the prevention of diseases. In this stage, its deficits produce the greatest amount of irreversible damage. This descriptive-transversal study was developed in the parish of San Pedro de la Bendita Catamayo Canton, which objective is to relate the consumption of micronutrients with anthropometry in a total of 57 boys and girls aged 6 to 36 months old. To obtain information, a structured interview was realized, which was applied to each mother, and the Body Mass Index (BMI) was determined to correlate it with micronutrient intake and the data was processed on the Excel calculation sheet. It was found that 47% of children consume micronutrients and 5% don't, in terms of body mass index in girls, showing that 96% are in normal ranges, 4% are overweight, and 94% are children within normal ranges 3% is overweight and 3% is underweight. It was concluded that the consumption of micronutrients doesn't affect directly to the anthropometry, besides statistically there is no significant correlation since R2 was obtained less than 0.5. Key words: Correlation, major infant, supplementation with Chis-paz, body mass index.